2003
DOI: 10.1163/156856203763572707
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and in vitro degradation of bioabsorbable self-expanding braided stents

Abstract: The aim of this study was to characterize the mechanical and self-expansion properties of braided bioabsorbable stents. In total four different stents were manufactured from PLLA fibres using a braiding technique. The changes in radial pressure stiffness and diameter recovery of the stents were determined initially, and after insertion and release from a delivery device. The braided stents were compared to three commercially available metallic braided stents. The changes in physical and mechanical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…Zilberman et al [24] reported a loss in radial compression strength for their PLLA stent designs with degradation time, which is also associated with reductions in elastic modulus and yield strain of the PLLA fibres. Nuutinen et al [25] carried out in vitro tests of a woven fibre polymeric braided stent subjected to radial compression in a pressurized chamber. The stent design did not perform well enough when made of biodegradable polymer, and the collapse pressure was still lower than its metal counterpart even with thicker fibres.…”
Section: Degradation Behaviourmentioning
confidence: 99%
“…Zilberman et al [24] reported a loss in radial compression strength for their PLLA stent designs with degradation time, which is also associated with reductions in elastic modulus and yield strain of the PLLA fibres. Nuutinen et al [25] carried out in vitro tests of a woven fibre polymeric braided stent subjected to radial compression in a pressurized chamber. The stent design did not perform well enough when made of biodegradable polymer, and the collapse pressure was still lower than its metal counterpart even with thicker fibres.…”
Section: Degradation Behaviourmentioning
confidence: 99%
“…Results showed that a successful biodegradable stent could be achieved by carefully balancing the mechanical properties of PLLA fibres and geometrical design of stents. Nuutinen et al [11] conducted in vitro tests of a woven fibre polymeric braided stent subjected to radial compression. The performance of such stents was not as good as metal ones, and the collapse pressure was found lower, even for thicker PLLA fibres.…”
Section: Introductionmentioning
confidence: 99%
“…This is because for an applied strain in the z direction, it is not possible for the main chain elements to avoid strain since the chains are physically elongated in the z direction. [18][19][20]. If a single crystal had a Young's modulus of 3x this value, at 0K the Young's modulus in the direction of the polymer chains may be expected to be between 54GPa (3x3x6GPa) and 192GPa (8x3x8GPa).…”
Section: Afem Program Setup and Polymer Structuresmentioning
confidence: 99%